“Sleep No More” Again: Melville's Rewriting of Book X of Wordsworth's Prelude - Duggan, Robert (Romanticism on the Net)

(untitled) (Université de Montréal, 2005)
AbstractIn the poem “The House-top” in his collection of Civil War poetry Battle-Pieces and Aspects of the War, Herman Melville attempts to rewrite the climatic “Sleep No More” episode of Book 10 of William Wordsworth’s Prelude to speak to the issues of post-Civil War America by revisiting the mix of violence and idealism Wordsworth encountered during the French Revolution. Hoping to escape Wordsworth’s loss of faith in ideals in the face of violence, Melville deconstructs Wordsworth’s use of language, stripping it of some of its timelessness for a greater time-full-ness to address the needs of the age rather than asking reality to conform to Romantic ideals, while also building on Wordsworth’s courageous example. Melville reconstructs the American narrative by rousing it from the “sleep” of Romantic idealism and calls his nation to awake to a new day of vast possibility in which exuberance and restraint coexist by demanding that ideals serve society rather than society blindly (and sometimes self-destructively) follow those ideals.